2018
DOI: 10.1242/bio.025734
|View full text |Cite
|
Sign up to set email alerts
|

An ancient conserved role for prion protein in learning and memory

Abstract: The misfolding of cellular prion protein (PrPC) to form PrP Scrapie (PrPSc) is an exemplar of toxic gain-of-function mechanisms inducing propagated protein misfolding and progressive devastating neurodegeneration. Despite this, PrPC function in the brain is also reduced and subverted during prion disease progression; thus understanding the normal function of PrPC in healthy brains is key. Disrupting PrPC in mice has led to a myriad of controversial functions that sometimes map onto disease symptoms, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
(125 reference statements)
0
11
0
Order By: Relevance
“…We recently engineered mutations of prp2 and were surprised to observe that the fish developed normally, with phenotypes that included deeply conserved roles in NMDA receptor dysregulation, learning/memory, and seizure susceptibility (16,27). This contrasted several works (including our own) using prion knockdown to produce dramatic early defects and suggested that PrP C is required for embryonic development (16,22,28).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…We recently engineered mutations of prp2 and were surprised to observe that the fish developed normally, with phenotypes that included deeply conserved roles in NMDA receptor dysregulation, learning/memory, and seizure susceptibility (16,27). This contrasted several works (including our own) using prion knockdown to produce dramatic early defects and suggested that PrP C is required for embryonic development (16,22,28).…”
mentioning
confidence: 86%
“…Indeed that notion was partially supported by examining the impact of PrP C loss on NMDA receptors, wherein the kinetics of channel closing were pushed toward hyperexcitability in both fish and mice (16). Further roles for PrP C at the synapse appear to be shared between mice and zebrafish, because its loss in either species leads to deficits in learning and memory (27,71).…”
Section: Prion Protein Has An Ancient and Conserved Role In Regulatinmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been decades of research, a full understanding of the physiological function of PrPc is lacking. Recently, some functions have been attributed to PrPc in the nervous system including neurite outgrowth [ 10 , 11 ], anti-apoptotic roles (during oxidative stress-induced cell death), pro-apoptotic roles (in ER stress) [ 12 , 13 ], Cu 2+ binding [ 14 , 15 ], synaptic plasticity [ 16 ], learning and memory [ 17 ], as well as sleep patterns [ 18 ]. The best strategy to better elucidate the physiological functions of PrPc is to identify and characterize its interacting protein partners because these interactions are most likely to be parts of physiological pathways in which PrPc plays a role ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The causes of PrP misfolding include sporadic conformational change, genetic mutations, or contact with infectious material already containing misfolded seeds leading to PrPSc-templated conversion of PrPC [ 20 ]. PrPC is very well conserved in mammals [ 21 , 22 ], and some domains (i.e., the C-terminal domain) are even preserved from fishes to mammals, probably indicating an important physiological function [ 23 , 24 , 25 , 26 ]. However, a clearly defined function is not yet specified but several, such as a role in regulating synaptic activity, as a receptor for toxic oligomers, as a regulator of neuritogenesis, and in contributing to peripheral myelination (reviewed in [ 27 ].…”
Section: Introductionmentioning
confidence: 99%